Conceptual approach to periodontal microsurgery: An insight - Riddhi Awasthi; Mohammad Jalaluddin; Urmi Agrawal; Dhirendra Kumar Singh (Wolters Kluwer Medknow Publications, 2022)
Periodontal treatment modalities have evolved since the 20th century. This era of periodontal treatment is progressing towards minimally invasive techniques. Nowadays, microscopes and surgical loupes are being used in different fields of dentistry. Periodontal surgeries like root coverage procedures, esthetic surgeries, scaling & root planing have also incorporated these methods for better esthetic results and patient compliance. Unlike in other fields of dentistry, there is more to be explored in the periodontal field with microsurgical methods. This article aims to discuss the evolution of periodontal treatment with microsurgical procedures and its principles. The literature concerning the efficacy of microsurgical approaches in treating periodontal diseases has been evaluated.